2023
DOI: 10.1186/s43593-022-00038-8
|View full text |Cite
|
Sign up to set email alerts
|

Computational coherent Raman scattering imaging: breaking physical barriers by fusion of advanced instrumentation and data science

Abstract: Coherent Raman scattering (CRS) microscopy is a chemical imaging modality that provides contrast based on intrinsic biomolecular vibrations. To date, endeavors on instrumentation have advanced CRS into a powerful analytical tool for studies of cell functions and in situ clinical diagnosis. Nevertheless, the small cross-section of Raman scattering sets up a physical boundary for the design space of a CRS system, which trades off speed, signal fidelity and spectral bandwidth. The synergistic combination of instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 119 publications
0
15
0
Order By: Relevance
“…This makes it possible to image lipid molecules with high spatial (hundreds of nanometer) and temporal resolution (microsecond per pixel) without the need to fix the cells. By tuning the vibrational resonance, a series of images can be acquired that cover a broad spectral window, known as hyperspectral imaging. , When integrated with high-dimensional data analysis, hyperspectral imaging has maximized chemical feature extraction, i.e., “fingerprinting” of the cellular lipids. Figure c shows typical label-free SRS images of protein and lipid in cells.…”
Section: Raman Imaging As a Powerful Tool For Studying Cellular Membr...mentioning
confidence: 99%
“…This makes it possible to image lipid molecules with high spatial (hundreds of nanometer) and temporal resolution (microsecond per pixel) without the need to fix the cells. By tuning the vibrational resonance, a series of images can be acquired that cover a broad spectral window, known as hyperspectral imaging. , When integrated with high-dimensional data analysis, hyperspectral imaging has maximized chemical feature extraction, i.e., “fingerprinting” of the cellular lipids. Figure c shows typical label-free SRS images of protein and lipid in cells.…”
Section: Raman Imaging As a Powerful Tool For Studying Cellular Membr...mentioning
confidence: 99%
“…All solid-state pulse lasers have unique advantages: small volume, high energy storage, and long life, which can meet the research and application needs in scientific research, 1 industry, medicine, military, and other fields. [2][3][4][5][6][7] The 2 µm band laser, which is safe for human eyes, is located at the atmospheric window and corresponds to the absorption peak of water.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, optical fiber sensors have been widely researched owing to the advantages of small size, long lifetime, strong flexibility, passive operation, and anti‐electromagnetic interference 7–13 . It has been demonstrated that the refractive index (RI) correlates better with salinity better than conductivity 14,15 .…”
Section: Introductionmentioning
confidence: 99%